2021
DOI: 10.1111/codi.15510
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the collateral system between the superior mesenteric artery and inferior mesenteric artery: a novel classification

Abstract: The aim of this study was to evaluate the arterial collateral vasculature between the superior mesenteric artery and the inferior mesenteric artery (IMA) from a surgical perspective.Method: A total of 107 fresh adult cadavers (94 male) were studied with emphasis on the vascular anatomy of the left colon. Dissections were carried out mimicking the anterior resection technique. The vasculature of the left mesocolon and the collaterals between the superior mesenteric artery and the IMA with respect to their relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…On the other hand, cadaver research for colon vessels has been reported. In the cadaver study, in all cases, the splenic flexure was supplied by the marginal artery, and there was no area with poor blood flow [ 36 ]. Improvements in computed tomography quality have enabled the vessel construction to be studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cadaver research for colon vessels has been reported. In the cadaver study, in all cases, the splenic flexure was supplied by the marginal artery, and there was no area with poor blood flow [ 36 ]. Improvements in computed tomography quality have enabled the vessel construction to be studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…In the cadaver study, in all cases, the splenic exure was supplied by the marginal artery and there was no area with poor blood ow. (33) Improvements in computed tomography quality have enabled the vessel construction to studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…For a colorectal surgeon, it is not sufficient to have basic knowledge of this discipline and an optimal level must be required. The paper published by Kuzu et al [1] in the present edition of Colorectal Disease highlights once again the importance of advances in this field. Vascular variability in the colonic splenic flexure is high and its classification and standardization will help during surgical procedures as well as planning future prospective studies.…”
mentioning
confidence: 94%
“…Vascularization of this area depends on the embryological union of the superior and inferior mesenteric vessels by means of vascular arches [1]. To perform a total mesocolic excision for a neoplasia of the colonic splenic flexure, all the arches should be included in the specimen considering the possible presence of metastatic lymph nodes along all of them.…”
mentioning
confidence: 99%